2018
DOI: 10.3390/ijms19123885
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Sphingosine Kinases and Sphingosine 1-Phosphate Receptors in the Mammalian Eye and Retina

Abstract: Sphingosine 1-phosphate (S1P) signaling regulates numerous biological processes including neurogenesis, inflammation and neovascularization. However, little is known about the role of S1P signaling in the eye. In this study, we characterize two sphingosine kinases (SPHK1 and SPHK2), which phosphorylate sphingosine to S1P, and three S1P receptors (S1PR1, S1PR2 and S1PR3) in mouse and rat eyes. We evaluated sphingosine kinase and S1P receptor gene expression at the mRNA level in various rat tissues and rat retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…SphK1 is expressed in photoreceptors whereas SphK1 and SphK2 are expressed both in ARPE19 and in human fetal RPE cells, implying these cells have the molecular machinery required for S1P synthesis (Abrahan et al, 2010; Zhu et al, 2010). A recent work has dissected the distribution of SphKs and S1PRs in mouse retina (Porter et al, 2018). SphK1 is low in most mouse ocular tissues and highest in the retina and optic nerve, whereas higher levels of SphK2 are observed in all mouse eye tissues.…”
Section: Sphingosine-1-phosphate a Formidable Double-edged Sword In mentioning
confidence: 99%
See 3 more Smart Citations
“…SphK1 is expressed in photoreceptors whereas SphK1 and SphK2 are expressed both in ARPE19 and in human fetal RPE cells, implying these cells have the molecular machinery required for S1P synthesis (Abrahan et al, 2010; Zhu et al, 2010). A recent work has dissected the distribution of SphKs and S1PRs in mouse retina (Porter et al, 2018). SphK1 is low in most mouse ocular tissues and highest in the retina and optic nerve, whereas higher levels of SphK2 are observed in all mouse eye tissues.…”
Section: Sphingosine-1-phosphate a Formidable Double-edged Sword In mentioning
confidence: 99%
“…S1p1 and S1p3 are expressed in the retina, while expression of S1p2 and S1p5 is minimal; S1P3 expression remains high and constant during retina development, whereas S1P1 increases gradually. Photoreceptors express both S1P1 and S1P3; S1P1 is highly expressed in RPE cells while S1P3 is localized in ganglion cells (Porter et al, 2018). Müller glial cells also show expression of SphK1 and S1P3 (Simón et al, 2015).…”
Section: Sphingosine-1-phosphate a Formidable Double-edged Sword In mentioning
confidence: 99%
See 2 more Smart Citations
“…However, we did not clarify the presence and activation dynamics of S1P in the retina. A report recently characterized the expression of SphKs and S1P receptors in rat and murine eyes, and found that the expression of SphK1, S1P2, and S1P3 in the retina is upregulated by light [15]. The findings strongly implied that S1P is associated with cell death and retinal degeneration in the mechanism of light-induced retinal degeneration.…”
Section: Introductionmentioning
confidence: 99%